Hyperreflective Foci and Subretinal Fluid Are Potential Imaging Biomarkers to Evaluate Anti-VEGF Effect in Diabetic Macular Edema - Qin, Shiyue; Zhang, Chaoyang; Qin, Haifeng; Xie, Hai; Luo, Dawei; Qiu, Qinghua; Liu, Kun; Zhang, Jingting; Xu, Guoxu; Zhang, Jingfa (Frontiers in Physiology, 2021)
Purpose: The aim was to investigate the effect and underlying mechanism of anti-vascular endothelial growth factor (anti-VEGF) in diabetic macular edema (DME) by optical coherence tomography angiography (OCTA). Methods: Twenty-five eyes in 18 treatment-naïve patients with DME were included. All eyes were imaged by OCTA at baseline and 1 week after monthly intravitreal aflibercept injection (IAI). Visual acuity was measured as best corrected visual acuity (BCVA). Additional parameters were evaluated by OCTA, including central macular thickness (CMT), the number of hyperreflective foci (HRF), foveal avascular zone (FAZ), vessel density (VD) in the deep capillary plexus (DCP), the en-face area of cystoid edema in DCP segmentation, and subretinal fluid (SRF) height. Results: The mean time between baseline and final follow-up by OCTA was 79.24 ± 38.15 (range, 28–163) days. Compared with baseline, BCVA was increased significantly after the 3rd IAI, while CMT was decreased significantly from the 1st IAI. SRF height and the area of cystoid edema in DCP segmentation were decreased significantly after the 2nd IAI compared with baseline. The number of HRF was decreased significantly after the 1st IAI (8.87 ± 9.38) compared with baseline (11.22 ± 10.63). However, FAZ’s area and perimeter as well as VD in DCP showed no significant changes post-treatment. Conclusion: Anti-VEGF is effective in treating DME, improving visual acuity and decreasing macular edema. The decreased HRF indicates anti-inflammatory effects of aflibercept to deactivate retinal microglia/macrophages. The decreased cystoid edema and SRF height indicated improved drainage function of Müller glial cells and retinal pigment epithelium after IAI.